ANALISIS SALURAN PEMASARAN UBI JALAR DI DESA CILEMBU KECAMATAN PAMULIHAN.KABUPATEN SUMEDANG - Rosida Susanti; Dini Rochdiani (Universitas Galuh Ciamis, 2021)
Sweet potato is a non-rice carbohydrate source that is highly nutritious and has a great potential as a support for food development. Sumedang Regency is one of the centers of sweet potato production in Indonesia, where the most popular sweet potatoes are those from Cilembu Village. This study aims to analyze (1) The channels and functions of sweet potato marketing in Cilembu Village. (2) Marketing margin, farmer’s share, and profit ratio and marketing cost of sweet potato in Cilembu Village. The selection of the research object was carried out purposively with the consideration that the research location was one of the sweet potato centers wich had its characteristics and were different from other regions. Respondents in this study were 20 farmers who were used as material to provide answers related to research taken on purpose (purposive) and 3 wholesalers, 3 small traders, and 4 middlemen taken by a snowball. The informants taken in this study were the head of the farmer group and the owner of the sweet potato processing industry. The analysis used in this research is descriptive. The result showed that (1) There were 4 marketing channels for sweet potatoes from farmers to the end consumers where there were 4 marketing institutions involved namely middlemen, wholesalers, small traders, and processing industries. The marketing function carried out by farmers in an exchange function and facilitating function, while the marketing function carried out by middlemen, large traders, small traders, and processing industries is an exchange function, a physical function, and a facility function.; (2) Judging from the value of the marketing margin, farmer’s share, and the R/C value of th the first, second, and fourth channels have achieved optimal performance. Meanwhile in the third channel, it has not achieved optimal performance because it has a low farmer’s share value even though the value of the marketing margin and R/C is quite high.